Manufacturing method of electrodeposited copper foil for lithium secondary batteries

A copper sulfate electrolyte with controlled additives and low organic content in electrodeposition ensures high initial tensile strength and thermal recrystallization properties, addressing the stability issues of conventional copper foils, enabling long-term storage and thermal stress resistance.

JP2025500108APending Publication Date: 2025-01-09CIRCUIT FOIL LUXEMBOURG
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024518630
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-20
Filing Date
2022-12-19
Publication Date
2025-01-09

AI Technical Summary

Technical Problem

Conventional electrodeposited copper foils for lithium secondary batteries suffer from room temperature recrystallization, leading to a decrease in tensile strength over time, which affects their mechanical stability and storage longevity, while foils designed for thermal stress recrystallization require rapid use due to similar issues.

Method used

A method for producing electrodeposited copper foil using a copper sulfate electrolyte with specific concentrations of copper ions, sulfuric acid, halogen ions, and thiourea-family additives, maintaining low total organic carbon content, to achieve high initial tensile strength and controlled recrystallization properties under thermal stress without significant room temperature degradation.

Benefits of technology

The produced copper foil exhibits stable tensile strength for weeks to months at room temperature and recrystallizes under thermal stress, maintaining mechanical integrity and suitability for lithium secondary battery applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025500108000003
    Figure 2025500108000003
  • Figure 2025500108000004
    Figure 2025500108000004
  • Figure 2025500108000005
    Figure 2025500108000005
Patent Text Reader

Abstract

The present invention relates to an electrodeposited copper foil and a method for producing the same. 2 It has a tensile strength of 50kgf / mm after 120 days at 35℃. 2 The copper foil exhibits a tensile strength of greater than 10 ...
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates generally to the field of electrodeposited copper foils, and more specifically to a method for producing electrodeposited copper foils for lithium secondary battery applications, as well as the resulting electrodeposited copper foils. [Background technology]

[0002] Lithium secondary batteries have many advantages over other secondary batteries, such as relatively high energy density, high operating voltage, and excellent storage and life characteristics, etc. Therefore, such lithium secondary batteries are widely used in various portable electronic devices such as personal computers, video cameras, mobile phones, portable CD players, PDAs, and electric vehicles.

[0003] Electrodeposited copper foils are usually used as negative electrode current collectors (anodes) in lithium secondary batteries. As is known, conventional electrodeposited copper foils are usually smooth on both sides to limit the difference in roughness between the "matte side" and the "shiny side", which affects the capacity retention rate.

[0004] Electrodeposited copper foils for lithium secondary batteries are produced in conventional electrolytic cells with a rotating cathode drum facing an insoluble anode. A typical electrolytic bath generally contains a copper sulfuric acid electrolyte with the following additives: 3-mercapto-1-propanesulfonic acid sodium salt (MPS) or bis(3-sulfopropyl) disulfide disodium salt (SPS), a nitrogen-containing organic leveler, and an organic polymer selected from high molecular weight polysaccharides.

[0005] The electrodeposited copper foil obtained by this manufacturing process typically has a roughness on both sides of less than 2.5 μm (Rz ISO), a tensile strength of about 320 MPa, and an elongation of about 8-10%.

[0006] As is known in the art, electrodeposited copper foils are subject to a room temperature recrystallization phenomenon, whereby when stored at room temperature, the electrodeposited copper foil gradually softens until its tensile strength stabilizes after recrystallization (at an average value of about 320 MPa, as shown above). The possible causes of the room temperature recrystallization phenomenon are the gradual relaxation of crystal defects due to electrolytic deposition and the deformation of the crystal lattice due to the adsorption of additives at the grain boundaries.

[0007] The mechanical behavior of electrodeposited copper foil over time is important to users, who want to be able to purchase electrodeposited copper foil that has a stable tensile strength during shipping and storage, and therefore exhibits the desired (nominal) tensile strength when brought to the production line for manufacturing battery electrodes, where room temperature recrystallization phenomena can result in adverse effects on mechanical properties.

[0008] For some applications, battery manufacturers require electrochemically deposited copper foils that are designed to recrystallize under thermal stress. These foils have high initial (i.e., as manufactured) tensile strengths (e.g., 45 kgf / mm 2 It exhibits a thermal stress of more than 30 kgf / mm2 and can recrystallize under the action of thermal stress during manufacturing processes, e.g. lamination. It has a tensile strength of 30 or 25 kgf / mm2. 2 and the elongation becomes very high (>10%).

[0009] Commercially available electrodeposited copper foils with recrystallization properties are notable prior art foils, such as PAF-1, which has a thickness between 6 and 10 μm and a thickness of about 46 kgf / mm 2 It has a high initial tensile strength of 23.5kgf / mm2 after thermal stress at 175℃ for 1 hour due to the designed recrystallization characteristics. 2 and elongation increases from 3-4% to over 8%.

[0010] Therefore, PAF-1 foil is characterized by its designed softening behavior due to recrystallization under severe thermal stress, which is desirable in the manufacturing process. The softening of the foil usually occurs during lamination processes, etc. However, one drawback of this foil is that it needs to be used fairly quickly after manufacturing, since the recrystallization occurs at room temperature.

[0011] In contrast, in other processes, users may wish to employ electrodeposited copper foils that do not exhibit such softening behavior. An example of such a commercially available foil is notable prior art foil 2, PAF2, which has a similar thickness range and surface roughness, does not recrystallize at room temperature or when subjected to thermal stress, and has high tensile strength without exhibiting stress relaxation properties. For example, PAF-2 foil has a tensile strength of about 46.4 kgf / mm 2 The tensile strength of the electrodeposited copper foil may be 8 μm, which has an initial tensile strength of 45.9 kgf / mm and does not change substantially over time. Even after being subjected to a thermal stress action at 175° C. for 1 hour, the tensile strength is still 45.9 kgf / mm 2 It is.

[0012] As can be appreciated, from a logistical standpoint, it is desirable for battery manufacturers to be able to store electrodeposited copper foil for a period of time without any change in its properties. As shown above, foils that have the design property of recrystallizing under the action of thermal stress, such as PAF-1, can exhibit altered tensile strength after several weeks at room temperature.

[0013] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a method for producing an electrodeposited copper foil which, by design, has the property of recrystallization under the action of thermal stress, but is unlikely to recrystallize at room temperature. Summary of the Invention

[0014] In order to achieve the above object, the present invention proposes a method for producing an electrodeposited copper foil, in which the electrodeposited copper foil is continuously formed in an electroforming cell including a rotating drum-shaped cathode, a stationary anode, and an electrolyte. According to the present invention, the electrolyte is - copper, preferably in the form of copper ions, in a concentration of at least 60 g / L; -sulfuric acid with a concentration of at least 60 g / L; - halogen ions at a concentration of less than 2 mg / L; and -thiourea-family electrolytic additive at a concentration between 0.001mg / L and 0.1mg / L; comprising or consisting of The TOC content in the electrolyte is less than 10 mg / L.

[0015] The present invention is based on the inventors' discovery of a specific bath composition with small amounts of additives that allows the production of electrodeposited copper foils that are more stable at room temperature than the electrodeposited copper foils of the prior art and therefore have a longer shelf life, while exhibiting recrystallization properties under the action of thermal stress and suitable for use in lithium secondary batteries. The present invention relies on the use of an electrolytic bath based on a copper sulfate electrolyte with only small amounts of additives as defined herein.

[0016] As defined in claim 1, the electrolyte has a low content of a thiourea-family electrolyte additive. Furthermore, the organic content of the electrolyte, i.e., total organic carbon, as conventionally reflected by TOC, is less than 10 mg / L. The low TOC value reflects the overall low content of organic additives in the electrolyte.

[0017] This method / electrolytic bath makes it possible to obtain electrolytic copper foils (also called electrolytic copper foils) that exhibit stable initial high tensile strength and recrystallization properties under thermal stress, allowing storage for several weeks to several months.

[0018] In particular, initial testing has confirmed that the method / electrolyte is capable of producing electrodeposited copper foil with the following mechanical properties: - Tensile strength at time of manufacture: 52kgf / mm 2 Ultra, especially 52-65kgf / mm 2 Range of; Tensile strength after 120 days storage at -35℃:>50kgf / mm 2 ; Tensile strength after thermal stress at -190℃ for 1 hour: 20 to 30kgf / mm 2 .

[0019] Therefore, the electrodeposited copper foil obtained by the method of the present invention has a compressive strength of 52 kgf / mm 2 The term "as-produced" usually refers to the foil as it is taken from the production line without any special annealing or heat treatment. The "as-produced" value can usually be measured within hours or days after production. The foil can recrystallize after severe thermal stressing, as shown by a typical thermal stress of 1 hour at -190°C, resulting in a lower tensile strength (<30 kgf / mm 2 ), and the elongation is very high (>10%).

[0020] In addition, during recrystallization at high temperatures, the tensile strength of foils with as-manufactured TS in the upper range is still 50 kgf / mm 2 or exceeds 52kgf / mm 2 Therefore, even after 120 days, the copper foil is quite stable at room temperature (up to 35°C).

[0021] As used herein, the term "recrystallization characteristics" refers to the ability of high tensile strength electrodeposited copper foils to undergo recrystallization under the action of a given thermal stress (time-temperature), thereby changing the microstructure from columnar to coarse grained, reducing the tensile strength to a lower range, and imparting high stretchability to the foil.

[0022] In this regard, the high tensile strength electrodeposited copper foil preferably has a strength of 50 kgf / mm 2 It has a tensile strength exceeding 30kgf / mm after thermal stress. 2 and the elongation can be greater than 10%. The test for recrystallization ability under thermal stress action may consist in thermal stressing by heating at 190°C for 1 hour, which usually results in complete recrystallization of the foil. This is the conventional test used in the lithium battery industry. A "short" version of the thermal stress alternative test may involve heating at 250°C for 2 minutes. A further "short" alternative test may be performed at 190°C for 1 hour. The shorter test is useful for the copper foil manufacturer to easily distinguish between foils that exhibit recrystallization property under thermal stress action and those that do not and maintain a high TS after thermal shock. Generally, the thermal stress to obtain complete recrystallization of the copper foil may be performed at temperatures ranging from 160 to 210°C for about 30 to 60 minutes, or at temperatures ranging from 230 to 260°C for several minutes.

[0023] "Tensile strength" herein conventionally refers to the ultimate tensile strength, i.e., the maximum stress that a material can withstand while being stretched / pulled before breaking. This is usually determined by performing a tensile test and recording a stress-strain curve. "Elongation" as used herein refers to the elongation at break, as can be determined from a tensile test.

[0024] In an embodiment, the electrodeposited copper foil has a copper purity of greater than 99.8% by weight, preferably greater than 99.9% by weight. The purity of the electrodeposited copper foil may be measured by electrogravimetry.

[0025] The electrolyte additive is a thiourea-family molecule present in the bath at a concentration of 0.1 mg / L or less.

[0026] In embodiments, the concentration of the thiourea-family electrolyte additive is 0.09 mg / L or less, particularly 0.085, 0.080, 0.075, 0.070, or 0.060 or less, and particularly 0.05 mg / L or less.

[0027] The thiourea-family electrolyte additive has a minimum concentration of 0.001 mg / L.

[0028] In embodiments, the thiourea-family electrolyte additive may have a minimum concentration of 0.003, 0.005, 0.007, 0.008, or 0.009.

[0029] The specified concentration of the thiourea-based electrolyte additive is important in electrolytic cells. It has been found to affect both the recrystallization characteristics and the room temperature stability, and therefore allows some control over these parameters. In particular, a concentration of thiourea-based electrolyte additive in the electrolyte exceeding 0.1 mg / L can impair the desired recrystallization characteristics under thermal stress, especially when the recrystallization is incomplete or the foil is damaged by stresses of 20 to 30 kgf / mm. 2 Conversely, if the thiourea-based electrolyte additive is not used, or if a concentration less than 0.001 mg / L is used, the resulting copper foil is not stable when stored at room temperature, and the shelf life of the foil is not extended.

[0030] As used herein, thiourea-family electrolyte additive refers to an organic additive containing a thiourea-function, i.e., having the following general structure: R2N-C(=S)-NR2, where R is hydrogen or any carbon chain, and the R groups may be the same or different.

[0031] In an embodiment, the thiourea-family electrolyte additive is selected from N-methyl-2-thiazolidinethione, 1-(2-hydroxyethyl)-2-imidazolidinethione, tetramethylthiourea, N,N'-diethylthiourea, N,N'-dimethylthiourea, N-allylthiourea, thiosemicarbazide, 2-imino-4-thiobiuret, 2-imidazolidinethione, acetylthiourea, 1,3-dibutyl-2-thiourea, and mixtures thereof.

[0032] In embodiments, the TOC in the electrolyte may be less than 7.5 mg / L, preferably less than 4.0 mg / L, more preferably less than 3.0 mg / L or less than 2.5 mg / L. In general, the TOC may be greater than or equal to 0.5, 1.0, or 1.5 mg / L.

[0033] In embodiments, the halide ions are chloride and / or bromide ions.

[0034] The halogen ions are present in the electrolyte at a concentration of less than 2 mg / L. The halogen ions are advantageously added up to a certain limit to control the tensile strength. In fact, if the halogen ion concentration in the electrolyte exceeds 2 mg / L, the tensile strength of the copper foil produced is reduced and cannot meet the desired requirements, especially when it is less than 52 kgf / mm 2 It will never exceed.

[0035] In embodiments, halogen ions may be present in the electrolyte at a concentration of less than 1 mg / L, preferably no more than 0.95, 0.9, 0.85 or 0.8 mg / L, more preferably no more than 0.6 or 0.5 mg / L. Preferably, the minimum concentration of halogen ions in the bath is 0.01, 0.02, 0.03, 0.04 or 0.05 mg / L.

[0036] All concentrations stated herein correspond to the concentrations of each of the various components in the electrolyte provided to the electroforming cell. The electrolyte continuously supplies the various components during operation of the electroforming cell, ensuring that the concentrations of the various components are always within their respective predetermined ranges. The baths may contain conventional unavoidable impurities and traces.

[0037] The resulting electrodeposited copper foil may be subjected to further subsequent processing steps as desired for the application. For example, a chromate coating may be applied to both sides of the electrodeposited copper foil.

[0038] Furthermore, first tests have shown that the electrodeposited copper foil produced according to the present invention has low profile roughness on both sides suitable for use in electrodes for lithium secondary batteries, in particular, both the matte side (electrolyte side) and the shiny side (drum side) have RzISO less than 2.5 μm.

[0039] Electrodeposited copper foil is connected between the cathode and anode at 40 and 80A / dm 2 Between 40 and 60 A / dm 2Between 45 and 55 A / dm 2 The current density may include a range between 0.25 and 1.0 V.

[0040] The electrolyte is preferably maintained at a temperature between 35 and 50°C.

[0041] Advantageously, the method is a continuous process and the electrolyte has an infinite life as long as there is a continuous supply of dissolved copper and additives.

[0042] In practice, the concentration of thiourea-based electrolyte additive in the electrolytic cell can be measured by high pressure liquid chromatography (HPLC), and the concentration of halogen can be measured by ion chromatography (IC).

[0043] According to another aspect, the invention relates to an electrolyte for the production of electrodeposited copper foils as claimed in claim 20.

[0044] What has been said regarding the advantages and embodiments of the method of the invention applies mutatis mutandis to the electrolyte of the invention.

[0045] In yet another aspect, the present invention also relates to an electrodeposited copper foil as claimed in claims 10 to 17. As mentioned above, the electrodeposited copper foil exhibits mechanical properties suitable for industrial use, particularly for the manufacture of electrodes for lithium secondary batteries. More specifically, the electrodeposited copper foil of the present invention has a high tensile strength that is stable over weeks / months and also exhibits recrystallization properties under the action of thermal stress.

[0046] According to another aspect, the invention relates to an electrode for a secondary battery comprising the above-mentioned copper foil as a current collector, as claimed in claim 18.

[0047] In lithium secondary batteries, for example, a foil comprising aluminum (Al) is generally used as a cathode (e.g., positive electrode) current collector in combination with a cathode active material, and the electrodeposited copper foil (i.e., obtained by the present process) is used as an anode (e.g., negative electrode) current collector in combination with an anode active material.

[0048] The anode active material layer can include an anode active material, and can further include conventional binders and / or conductive materials known in the art.

[0049] The anode active material is not particularly limited as long as it is a compound capable of intercalating and deintercalating ions. Non-limiting examples of applicable anode active materials include, but are not limited to, carbon-based and silicon-based anode active materials, as well as lithium metal or its alloys, and TiO2, SnO2, and Li4Ti5O2, which are capable of occluding and releasing lithium and have a potential of less than 2 V relative to lithium. 12 Other metal oxides such as may be used.

[0050] The above-mentioned method for manufacturing a secondary battery electrode using copper foil is well known to those skilled in the art to which the present invention pertains, and therefore a detailed description thereof will be omitted.

[0051] According to yet another aspect, the present invention relates to a secondary battery as claimed in claim 19. The secondary battery may be a lithium secondary battery, in particular including lithium metal secondary batteries, lithium ion secondary batteries, lithium polymer secondary batteries, lithium ion polymer secondary batteries, etc. The secondary battery may include a liquid or solid electrolyte, for example of the polymer, oxide or sulfide family.

[0052] In one example, a lithium secondary battery may include a cathode (e.g., a positive electrode) including a cathode active material, an anode (negative electrode) including an anode active material, and an electrolyte interposed between the cathode and the anode. In addition, the battery may further include a separator.

[0053] Lithium secondary batteries may be manufactured using conventional methods known in the art, for example, by interposing a separator between the cathode and anode, and then introducing an electrolyte with an electrolyte additive.

[0054] The electrolyte may include a conventional lithium salt known in the art; and an electrolyte solvent.

[0055] As the separator, a porous separator such as a polypropylene-, polyethylene-, or polyolefin-based porous separator can be used, or an organic / inorganic composite separator containing an inorganic material can be used.

[0056] In this specification, the terms "TOC amount," "TOC content," and "TOC," which conventionally refer to the total amount of organic carbon present in an electrolyte (i.e., the total content of organic carbon in an electrolyte), are used as synonyms and have the same meaning, respectively.

[0057] In this specification, any given numerical value encompasses a range of values ​​from -10% to +10% of that numerical value, preferably a range of values ​​from -5% to +5% of that numerical value, and more preferably a range of values ​​from -1% to +1% of that numerical value.

[0058] Further details and advantages of the invention will become apparent from the following detailed description of some non-limiting embodiments, with reference to the accompanying drawings. [Brief description of the drawings]

[0059] The invention will now be described, by way of example only, with reference to the accompanying drawings in which: [Figure 1] FIG. 1 is a schematic diagram of an electroforming cell. [Diagram 2]A plot of tensile strength versus temperature is shown, along with SEM (scanning electron microscope) views of the copper foil before and after heat treatment, along with corresponding sketches of the microstructure. [Diagram 3] 1 is a graph showing the change in tensile strength (TS) with respect to thermal stress applied for 10 minutes at various temperatures. [Figure 4] 1 is a graph showing the change in TS over time when copper foil is stored at 35° C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0060] First, the operating principle of the electroforming cell will be explained with reference to FIG. 1, which is a schematic diagram of the electroforming cell. As described above, the present invention provides a method for producing electrodeposited copper foil, i.e., a method for producing electrodeposited copper foil that is continuously formed in an electroforming cell, as well as an electrolyte for producing electrodeposited copper foil, i.e., an electrolyte for producing electrodeposited copper foil that has very low surface roughness and is free of defects.

[0061] Electrodeposited copper foil is produced by using an electroforming cell 10 (known in the industry as a plating machine) to produce a copper foil 18, as shown in FIG. 1. In the electroforming cell 10, an electrolyte 12 passes through an apparatus including a rotating drum-shaped cathode 14 (having a stainless steel or titanium surface) and a stationary anode 16 (a lead or titanium electrode coated with a noble metal oxide) opposite the cathode 14. An electric current is passed through both electrodes 14, 16, thus depositing copper to a desired thickness on the surface of the cathode 14 to form the electrodeposited copper foil 18. The electrodeposited copper foil 18 is then peeled from the surface of the cathode 14 and wound on a storage reel 20. The foil thus prepared is generally referred to as untreated copper foil.

[0062] In a subsequent step, the electrodeposited copper foil 18 may be subjected to a chromate coating step (not shown) - typically on both sides of the foil - and / or any other suitable treatment step on one or both sides of the foil for use in the lithium battery industry.

[0063] The electrodeposited copper foil produced by the present invention has high as-produced tensile strength and is characterized by its recrystallization characteristics under the action of thermal stress, by design. That is, the foil is designed by its manufacturing method to show a tensile strength transition when subjected to severe thermal stress. That is, the foil is manufactured at a tensile strength of typically 50-52 kgf / mm. 2 Above 50 and 65 kgf / mm 2 After thermal stressing, the tensile strength is between 20 and 45 kgf / mm2, depending on the initial tensile strength and the thermal stress conditions. 2 In this case, the elongation also exceeds 10% and increases to 20-25%.

[0064] This recrystallization characteristic of the microstructural changes during heating of the electrodeposited copper foil is shown in Figure 2 (Tensile strength vs. heat treatment temperature (duration = 30 min)). As the plot shows, there is a significant decrease in TS as the treatment temperature increases. The electrodeposited copper foil exiting the electroforming cell exhibits a columnar grain structure as shown on the left side of Figure 2. The heat applied during the thermal stressing process causes a sort of annealing of the copper foil during which the crystals are rearranged to form a rather coarse grain as shown on the right side of Figure 2. This coarse grain structure reduces the tensile strength.

[0065] A high initial tensile strength is desirable for handling purposes, allowing for thinner foil thicknesses and operating under higher active loads.

[0066] On the other hand, considering the use of copper foil integrated into the electrodes of LIB batteries, a softer behavior is preferred. During the manufacture of the battery, the copper foil is subjected to thermal stresses. During this process, it is desirable for the copper foil to recrystallize in order to obtain a high elongation copper foil that can better cope with the swelling of the anode during charging and discharging of the battery (especially for anodes with high Si content - or other high swelling materials).

[0067] Thus, the electrodeposited copper foils produced according to the process of the present invention have recrystallization characteristics by design. However, as will be apparent from the examples below, electrodeposited copper foils produced according to the process of the present invention can be stored at room temperature up to 35° C. for up to 120 days without substantial change in tensile strength.

[0068] The properties of the foils of the present invention (produced according to the present process) can also be seen in Figures 3 and 4 which compare the copper foil of the present invention (round) with the prior art foil PAF-1 (triangle) described in the Background section.

[0069] The plot in Figure 3 shows the same behavior as in Figure 2 for thermal stress applied for 10 minutes at temperatures ranging from 20°C to 250°C. As can be seen, the foil of the present invention has a high initial tensile strength, which decreases significantly under thermal stress above 160°C. The recrystallization characteristics of the foil of the present invention are comparable to conventional recrystallized foils such as PAF-1. However, as is clear from Figure 4, the copper foil of the present invention has a fairly stable tensile strength at room temperature compared to conventional recrystallized foils such as PAF-1. In particular, the TS is 50 kgf / mm even after 120 days at 35°C. 2 exceeds.

[0070] example Electrodeposited copper foils were produced using either the method according to the invention (Examples 1 to 3) or comparative methods which do not form part of the present invention (Comparative Examples 1 to 4). Various example electrolyte compositions are shown in Table 1 below, where MPS stands for 3-mercapto-1-propanesulfonate and HEC stands for hydroxyethyl cellulose.

[0071] The concentrations shown in Table 1 correspond to the concentrations of the various compounds in the electrolyte supplied to the electroforming cell. Before starting the electroforming cell (or plating machine), each electrolyte is prepared by solubilizing the compounds shown in Table 1 in an appropriate amount of water. Each electrolyte also contains copper, which is oxidized to metallic copper and dissolved in the electrolyte with sulfuric acid. The copper concentration is 80 g / L. During operation of the electroforming cell, each electrolyte is continuously supplied with the various components to ensure that the concentrations of the various components are always within the respective predetermined ranges.

[0072] [Table 1]

[0073] It should be noted that TOC is a measure of the total organic carbon of an electrolyte solution, which reflects the total organic content of the electrolyte solution. It is not an additive, but a measure of organic content as known in the art. The rather low TOC content reflects the fact that the electrolyte is low in additives.

[0074] The resulting (i.e., as-produced) electrodeposited copper foils were then analyzed to determine mechanical properties such as tensile strength and elongation. The measurements obtained are reported in Table 2 under "As-Produced." The electrodeposited copper foils obtained in Examples 1 to 3 all had a thickness of 8 μm and exhibited an RzISO roughness of less than 2.5 μm on both sides.

[0075] Some of these foils were subjected to a thermal stress at 190°C for 1 hour, the resulting values ​​of tensile strength and elongation are given in columns 4-5 of Table 2. Another part of these foils was stored at 35°C for 120 days, the subsequent measurements of tensile strength and elongation are given in columns 6-7 of Table 2.

[0076] [Table 2]

[0077] The measurements in Table 2 were carried out on samples subjected to the action of thermal stress at room temperature, ie after cooling. As is clear, the electrodeposited copper foils of Examples 1 to 3 have a compressive strength of 50 kgf / mm 2 It has a high initial tensile strength of .GAMMA. and shows recrystallization behavior after severe thermal stress (here, 190°C for 1 hour), but can be stored for about 3 months without a significant decrease in tensile strength.

[0078] In contrast, the foil of Comparative Example 1 - made from an electrolyte with MPS, HEC and gelatin as additives - has a low and stable tensile strength without recrystallization properties under the given thermal stress action. Using copper sulfate electrolyte with chloride as the sole additive results in foils with high initial tensile strength and recrystallization properties after thermal stressing, as shown in Comparative Example 2. However, the foil suffers from substantial room temperature recrystallization, as after 120 days it has less than half the tensile strength of the as-manufactured foil.

[0079] Comparative Examples 3 and 4 show that the addition of thiourea-family additives (in the range of 0.5 to 5 mg / L) to the electrolyte of Example 2 stabilizes the (high) tensile strength at room temperature, but the foil does not exhibit the desired recrystallization properties under the action of thermal stress.

[0080] As a result, only the electrolyte compositions according to the present invention, i.e., those containing halogen ions and thiourea-family electrolyte additives within the specified concentrations, allow the production of electrodeposited copper foils with high tensile strength that are stable over weeks / months and exhibit recrystallization properties under the action of thermal stress.

[0081] Determination of tensile strength and elongation The tensile strength measurements were carried out in accordance with the standard IPC-TM-650 No. 2.4.18. Tensile strength, more precisely ultimate tensile strength, was measured using a universal testing machine Instron 5564 SP 2962 (UTM) with a gauge length of 2.0 inches (50.8 mm). The crosshead speed was set at 2.0 inches / min. Samples were cut into strips 0.5 inches wide and 6 inches long.

[0082] Determining the surface roughness of matte surfaces The roughness of the copper foil was measured with a contact profilometer, which consists of a diamond stylus sliding over the surface. From this measurement, a 2D profile of the surface is created and Rz is calculated as the average distance between the highest peak and the lowest valley over eight sampling lengths. Here, surface roughness Rz refers to ISO (4287:1997).

[0083] Determination of TOC content of electrolyte solutions TOC (total organic carbon) analysis is performed using a total carbon analyzer. Any suitable TOC analysis device / method can be used. As known in the art, TOC analyzers determine the amount of carbon in a water sample. Currently, commercially available TOC analyzers actually measure total carbon, so the TOC analysis must always take into account some inorganic carbon present. One analytical technique involves a two-step process, commonly referred to as TC-IC. It measures the amount of inorganic carbon (IC) released from an acidified aliquot of the sample and the amount of total carbon (TC) present in the sample. TOC is calculated by subtracting the IC value from the TC of the sample. In another form, the sample is oxidized to release carbon dioxide, which is measured as inorganic carbon (IC), and the remaining non-purgeable organic carbon (NPOC) is oxidized and measured. This is called TIC-NPOC analysis. A more common method is to acidify the sample again to a pH value below 2 and measure the TOC in the sample directly, but release the IC gases, in this case to the air rather than for measurement. Any remaining unsweepable CO2 gas contained in the liquid aliquot is then oxidized to release gases that are sent to a detector for measurement.

[0084] TOC analysis, whether by TC-IC or NPOC methods, can be divided into three main steps: 1. Acidification 2. Oxidation 3. Detection and Quantification The first step is acidification of the sample to remove IC and sweepable organic carbon gases. By adding acid and purging with an inert gas, all bicarbonate and carbonate ions are converted to carbon dioxide and this IC product is vented along with any sweepable organic carbon (POC) that was present. These gases are either released to the detector for measurement or released to the air depending on the type of analyte being targeted: TC-IC for the former, or TOC (non-sweepable organic carbon) for the latter.

[0085] The second step is to oxidize the remaining carbon in the sample in the form of carbon dioxide (CO2) and other gases. Modern TOC analyzers perform this oxidation step by either high temperature combustion (sometimes using a Pt catalyst), high temperature catalytic oxidation, photooxidation, thermochemical oxidation (mainly using a heated persulfate source), photochemical oxidation (mainly using ultraviolet light and a persulfate source), or electrolytic oxidation.

[0086] The third step is the detection and quantification of the formed CO2. Conductivity, ultraviolet spectrophotometry, and non-dispersive infrared (NDIR) are the three most common detection methods used in commercial TOC analyzers.

[0087] This TOC measurement method One detailed but non-limiting method for analyzing electrolytic baths to determine the TOC content is disclosed below. This method was used to determine the TOC of the examples and counter-examples in Table 1. According to this method, the TOC (total organic carbon) analysis is performed using a wet-chemistry TOC analyzer that operates with both an oxidizing agent (peroxydisulfate) and a highly effective UV radiation source for sample oxidation. The TOC measurement method performed is the TIC-NPOC analysis.

[0088] The (electrolyser) sample is diluted (preferably 5-fold) with ultrapure water (to avoid detector saturation due to complex matrix effects) and acidified with 10% w / w phosphoric acid to a pH below 2 in order to remove inorganic carbon (dissolved CO2 from the atmosphere) from the sample. Indeed, in an acidic medium, carbonic acid is present - not in the form of bicarbonate - in a protonated form, allowing an almost complete removal of CO2 from the solution due to the equilibrium between CO2 and carbonic acid through a dehydration reaction. The resulting CO2 can be diffused from the sample to the waste by a vector gas (see below).

[0089] The organic molecules contained in the sample are then completely oxidized (to CO2 gas) by a combination of a strong oxidizing chemical (peroxydisulfate) and a highly effective UV radiation source. A vector gas (nitrogen) is then injected into the sample to transport this carbon dioxide from the sample to the detector, where the CO2 molecules are then detected from the mixture formed with the carrier gas using an infrared detector (a focused emission NDIR detector).

[0090] The TOC analyzer used to determine the TOC of the examples and counterexamples in Table 1 is a commercial instrument model "MULTI N / C UV HS BU" manufactured by Analytik Jena. The acidification and all subsequent steps are carried out automatically inside the machine (only the dilution step is performed manually / externally).

Claims

1. 1. A method for producing an electrodeposited copper foil, in which the electrodeposited copper foil is continuously formed in an electroforming cell containing a rotating drum-shaped cathode, a stationary anode, and an electrolyte, comprising: The electrolyte is Copper, preferably in the form of copper ions, at a concentration of at least 60 g / L; Sulfuric acid at a concentration of at least 60 g / L; Halogen ions at a concentration of less than 2 mg / L; and a thiourea-family electrolyte additive at a concentration between 0.001 mg / L and 0.1 mg / L; The TOC content in the electrolyte is less than 10 mg / L; Manufacturing method of electrodeposited copper foil.

2. 2. The method of claim 1, wherein halogen ions are present in the electrolyte at a concentration of less than 1 mg / L, preferably no more than 0.95, 0.9, 0.85 or 0.8 mg / L, more preferably no more than 0.6 mg / L.

3. 3. The process according to claim 1 or 2, wherein the halogen ions are chloride and / or bromide ions.

4. 4. The method of any one of claims 1 to 3, wherein the thiourea-family electrolyte additive is present in the electrolyte at a concentration of less than or equal to 0.09 mg / L, preferably less than or equal to 0.085, 0.080, 0.075, 0.070, more preferably less than or equal to 0.05 mg / L.

5. 5. The method of any one of claims 1 to 4, wherein the thiourea-family electrolyte additive is selected from N-methyl-2-thiazolidinethione, 1-(2-hydroxyethyl)-2-imidazolidinethione, tetramethylthiourea, N,N'-diethylthiourea, N,N'-dimethylthiourea, N-allylthiourea, thiosemicarbazide, 2-imino-4-thiobiuret, 2-imidazolidinethione, acetylthiourea, 1,3-dibutyl-2-thiourea, and mixtures thereof.

6. 6. The method of claim 1, wherein the TOC in the electrolyte is less than 2.5 mg / L.

7. 7. The method of claim 1, wherein the copper is added to the electrolyte as copper sulfate.

8. 8. The method of claim 1, wherein the copper and sulfuric acid are each present in the electrolyte at a concentration between 60 and 100 g / L.

9. The electrodeposited copper foil is connected between the cathode and anode at 40 and 80 A / dm 2 , preferably 40 and 60 A / dm 2 , more preferably 45 and 55 A / dm 2 The method of claim 1 , wherein the thin film is formed by applying a current density ranging from 0.01 to 0.5%.

10. 10. The method of any one of claims 1 to 9, wherein the electrolyte temperature is maintained between 35 and 50°C.

11. Electrodeposited copper foil is 52 kgf / mm 2 It has a tensile strength of 50 kgf / mm after 120 days at 35°C. 2 25. An electrodeposited copper foil, in particular produced by the method according to any one of claims 1 to 10 or by using the electrolyte according to any one of claims 20 to 24, which exhibits a tensile strength of greater than 1000 MPa and exhibits recrystallization properties under thermal stress.

12. Electrodeposited copper foil: 52 to 65 kgf / mm 2 12. The electrodeposited copper foil of claim 11 having an as-manufactured tensile strength in the range of

13. After thermal stress at 160°C for 10 minutes, the electrolytic copper foil has a compressive strength of about 35 to 45 kgf / mm 2 The electrodeposited copper foil according to claim 11 or 12, having a tensile strength of

14. After one hour of thermal stress at 190°C, the electrolytic copper foil has a strength of about 20 to 30 kgf / mm 2 14. The electrodeposited copper foil according to claim 11, 12 or 13, having a tensile strength of

15. 15. The electrodeposited copper foil of any one of claims 11 to 14, wherein the electrodeposited copper foil has an elongation in the range of 10 to 25% after thermal stressing at 190°C for 1 hour.

16. 16. The electrodeposited copper foil of claim 11, wherein the electrodeposited copper foil has a surface roughness RzISO of 2.5 μm or less.

17. 17. The electrodeposited copper foil of any one of claims 11 to 16, wherein the electrodeposited copper foil has a thickness between 4 and 12 μm.

18. 18. The electrodeposited copper foil of any one of claims 11 to 17, wherein the electrodeposited copper foil has a copper purity of greater than 99.8 wt-%.

19. 19. An electrode for a secondary battery comprising the electrodeposited copper foil of any one of claims 10 to 18 and an active material layer disposed on the copper foil.

20. A secondary battery comprising the electrode of claim 19.

21. Copper, preferably in the form of copper ions, at a concentration of at least 60 g / L; Sulfuric acid at a concentration of at least 60 g / L; Halogen ions at a concentration of less than 2 mg / L; and Thiourea-family electrolyte additive at a concentration between 0.001 mg / L and 0.1 mg / L; Including, An electrolyte for producing electrodeposited copper foil, wherein the TOC content in the electrolyte is less than 10 mg / L.

22. 22. The electrolyte of claim 21 , wherein halogen ions are present in the electrolyte at a concentration of less than 1 mg / L, preferably no more than 0.95, 0.9, 0.85 or 0.8 mg / L, more preferably no more than 0.6 mg / L.

23. 23. An electrolyte according to claim 21 or 22, wherein the halogen ions are chloride and / or bromide ions.

24. 24. The electrolyte of any one of claims 21 to 23, wherein the thiourea-family electrolyte additive is present in the electrolyte at a concentration of 0.09 mg / L or less, preferably 0.085, 0.080, 0.075, 0.070 or less, more preferably 0.05 or less.

25. 25. The electrolyte of any one of claims 21 to 24, wherein the thiourea-family electrolyte additive is selected from N-methyl-2-thiazolidinethione, 1-(2-hydroxyethyl)-2-imidazolidinethione, tetramethylthiourea, N,N'-diethylthiourea, N,N'-dimethylthiourea, N-allylthiourea, thiosemicarbazide, 2-imino-4-thiobiuret, 2-imidazolidinethione, acetylthiourea, 1,3-dibutyl-2-thiourea, and mixtures thereof.

26. 26. The electrolyte of any one of claims 21 to 25, having a TOC of less than 2.5 mg / L.

Citation Information

Patent Citations

  • Electrolytic copper foil for lithium secondary battery and lithium secondary battery including same

    CN106663816A

  • High fatigue ductility electro-deposited copper foil

    JP2003201592A

  • Copper wire and a process for making same

    WO2000048758A1

  • Electrolytic copper foil and method for producing same

    WO2020121894A1